Advantages of trend analysis in stability studies for prediction of potential OOS result within estimated shelflife of medicinal product - Milena Nanov; Sanja Despotovska; Gordana Mitrovska; Vasilka Dubrova Koceva; Jelena Acevska (Makedonsko Farmacevtski Bilten)
Stability studies are crucial for pharmaceutical product registration, providing vital data to assess batch-to-batch consistency, monitor critical quality attributes, and ensure the product's quality, safety, and efficacy over its entire shelf life. Identifying potential issues such as potential out-of-specification (OOS) results and ensuring data quality is often facilitated by employing objective methods for trend analysis of stability data. The goal of the research was to explore the advantages of trend analysis in stability studies, highlighting its significance in forecasting OOS results and ensuring the consistent performance of pharmaceutical products within their estimated shelf life. To evaluate stability data and find the pattern of data that indicates change over time, stability studies for Lisinopril/Amlodipine tablets 20mg/10mg were subjected to trending analysis based on data from annual or routine stability studies. The trending analysis was performed to evaluate whether the data demonstrates increasing or decreasing trend (change of mean) for the stability indicating parameters over time or the data indicate no discernible change at all, as well as predicting potential OOS results during shelf life. Regression analysis as a statistical tool for trending analysis, is considered an appropriate approach to evaluating the stability data for a quantitative attribute.